Elements of Benefit in Islamic Jurisprudence - Abu-Mounes, Raed Nasri; Budaer, Dua Mahmood (Dirasat: Shari’a and Law Sciences, 2024)
Objectives: This study aims to clarify the elements of benefits and review their dimensions that address many possibilities, by tracking what the Sharia jurists presented about benefit, taking into consideration the stages of development of benefits in the modern era. Methods: The study employed appropriate scientific methods, represented by the inductive approach to the opinions and ideas discussed by scientists about how to reach the state of information appropriate to the issues related to it. The descriptive approach was also used when presenting the elements of the benefit and the branches that fall under it after using the analytical approach to explain the reason for the regularity of these elements under certain divisions and special considerations that make it easier to know what contributes to the production of utility and causes its difference. Results: The study showed that the benefit depends in its production on basic elements, which are represented by resources and the interactive activities between them under specific conditions and the many possibilities that fall under it come with material dimensions such as human resources, plant and animal resources or moral dimensions such as applications and programs that affect the amount and description of the benefits. Conclusions: This study has concluded that the main reason for the diversity and difference of benefits is the dependence of their existence abroad on elements that have material or moral dimensions of varying descriptions and quantities, and this study came to recommend researching the Sharia rulings on the elements of the benefit.